Expanding the apelin receptor pharmacological toolbox using novel fluorescent ligands - Williams, Thomas L.; Macrae, Robyn G. C.; Kuc, Rhoda E.; Brown, Alastair J. H.; Maguire, Janet J.; Davenport, Anthony P. (Frontiers in Endocrinology, 2023)
Introduction The apelin receptor binds two distinct endogenous peptides, apelin and ELA, which act in an autocrine/paracrine manner to regulate the human cardiovascular system. As a class A GPCR, targeting the apelin receptor is an attractive therapeutic strategy. With improvements in imaging techniques, and the stability and brightness of dyes, fluorescent ligands are becoming increasingly useful in studying protein targets. Here, we describe the design and validation of four novel fluorescent ligands; two based on [Pyr1]apelin-13 (apelin488 and apelin647), and two based on ELA-14 (ELA488 and ELA647). Methods Fluorescent ligands were pharmacologically assessed using radioligand and functional in vitro assays. Apelin647 was validated in high content imaging and internalisation studies, and in a clinically relevant human embryonic stem cell-derived cardiomyocyte model. Apelin488 and ELA488 were used to visualise apelin receptor binding in human renal tissue. Results All four fluorescent ligands retained the ability to bind and activate the apelin receptor and, crucially, triggered receptor internalisation. In high content imaging studies, apelin647 bound specifically to CHO-K1 cells stably expressing apelin receptor, providing proof-of-principle for a platform that could screen novel hits targeting this GPCR. The ligand also bound specifically to endogenous apelin receptor in stem cell-derived cardiomyocytes. Apelin488 and ELA488 bound specifically to apelin receptor, localising to blood vessels and tubules of the renal cortex. Discussion Our data indicate that the described novel fluorescent ligands expand the pharmacological toolbox for studying the apelin receptor across multiple platforms to facilitate drug discovery.